Eliminating the head instability of an axial-flow pump using axial grooves - Goltz, Isabel; Kosyna, Günter; Delgado, Antonio (Proceedings of the Institution of Mechanical Engineers Part A-Journal of Power and Energy, 2013)
This article presents a new type of casing treatment which completely eliminates the drop in the head characteristic of a single-stage, axial-flow pump without any noticeable negative effect on the pump efficiency. The casing treatment consists of 60 shallow axial grooves, which are located only in front of the rotor. These shallow axial grooves differ from other commonly investigated types of casing treatments with respect to their mechanism of action. For a qualitative as well as a quantitative analysis of the mechanism of action of grooves, oil flow pictures were taken and also radial velocity profiles were measured using calibrated pressure probes. These investigations reveal that, unlike other types of casing treatments, the grooves do not delay the onset of stall by controlling the rotor inflow before reaching the stall point. However, when stall occurs, the shallow axial grooves reduce the detrimental swirl component of the stall cell, which otherwise leads to the drop in pump head at the stall point. The pump efficiency at design is not affected by these types of grooves. In deep stall, the efficiency is even higher for the grooved casing due to better inlet flow conditions. © IMechE 2013.
UnivIS-Import:2015-03-09:Pub.2013.tech.ITC.stmmec.elimin
Keywords: Axial grooves; Axial-flow pump; Casing treatment; Stall; Stall margin improvement